Sensing Bisphenol A by Means of Surface-Enhanced Raman Spectroscopy and DFT Calculations to Elucidate the Enhancement Mechanism That Dominates the Spectrum - Lemos de Souza, Michele; Valdivia Mantas, Samuel; Otero-Fernández-de-Molina, Juan Carlos; López-Tocón, Isabel (IOAP-MDPI, 2023)
Surface-Enhanced Raman Spectroscopy (SERS) was employed as a spectroscopic tool to detect Bisphenol A (BPA), a building block in polycarbonate and epoxy resins or an additive in other polymer plastics like PVC, which has an endocrine disruptor effect. Silver nanoparticles (AgNPs) synthesized by using different reducing agents such as hydroxylamine (Ag@HX), citrate (Ag@Cit), borohydride (Ag@BH), and β-cyclodextrin (Ag@βCD) were employed, aiming to select the best standard SERS substrate. The lowest limit of quantification was reached at a concentration of 0.01 mM (2.3 μg/mL) of a sonicated aqueous solution by using Ag@Cit NPs and identifying two enhanced bands recorded at about 350 and 460 cm−1. In order to gain insight into the nature of the enhanced bands, and therefore into which mechanism governs the SERS signal, electrochemical spectra recorded at different electrode potentials were acquired and TD-DFT calculations were applied to a neutral silver complex of BPA, Ag2-BPA, and to its monohydroxylated chemical specie, Ag2-BPA(OH), which is present in sonicated solution. The calculated electronic structure and the resonance Raman spectra point out that a surface plasmon-like resonance inside the silver cluster dominates the SERS spectrum corresponding to the physisorbed BPA(OH) species, a charge transfer enhancement mechanism or an intramolecular resonance transition localized in the phenolic framework was then discarded
Keywords: Espectroscopía; SERS spectroscopy; Nanoparticles; Bisphenol A; DFT calculations